High Streptococcus pneumoniae colonization prevalence among HIV-infected Kenyan parents in the year before pneumococcal conjugate vaccine introduction. Issue 1 (December 2015) - Conklin, Laura; Bigogo, Godfrey; Jagero, Geofrey; Hampton, Lee; Junghae, Muthoni; da Gloria Carvalho, Maria; Pimenta, Fabiana; Beall, Bernard; Taylor, Thomas; Plikaytis, Brian; Laserson, Kayla; Vulule, John; et al.
Abstract Background Streptococcus pneumoniae is a leading cause of pneumonia, meningitis and sepsis in developing countries, particularly among children and HIV-infected persons. Pneumococcal oropharyngeal (OP) or nasopharyngeal (NP) colonization is a precursor to development of invasive disease. New conjugate vaccines hold promise for reducing colonization and disease. Methods Prior to introduction of 10-valent pneumococcal conjugate vaccine (PCV10), we conducted a cross-sectional survey among HIV-infected parents of children <5 years old in rural Kenya. Other parents living with an HIV-infected adult were also enrolled. After broth enrichment, NP and OP swabs were cultured for pneumococcus. Serotypes were identified by Quellung. Antimicrobial susceptibility was performed using broth microdilution. Results We enrolled 973 parents; 549 (56.4 %) were HIV-infected, 153 (15.7 %) were HIV-uninfected and 271 (27.9 %) had unknown HIV status. Among HIV-infected parents, the median age was 32 years (range 15-74) and 374/549 (68 %) were mothers. Pneumococci were isolated from 237/549 (43.2 %) HIV-infected parents and 41/153 (26.8 %) HIV-non-infected parents (p  = 0.0003). Colonization with PCV10 serotypes was not significantly more frequent in HIV-infected (12.9 %) than HIV-uninfected parents (11.8 %;p  = 0.70). Among HIV-infected parents, cooking site separate from sleeping area and CD4 count >250 were protective (OR = 0.6; 95 % CI 0.4, 0.9 and OR = 0.5; 95 % CI 0.2, 0.9, respectively); other associations were not identified. Among 309 isolates tested from all parents, 255 (80.4 %) were penicillin non-susceptible (MIC ≥0.12 μg/ml). Conclusions Prevalence of pneumococcal colonization is high among HIV-infected parents in rural Kenya. If young children are the pneumococcal reservoir for this population, PCV10 introduction may reduce vaccine-type colonization and disease among HIV-infected parents through indirect protection.